LEFT VENTRICULAR GEOMETRY IN CHILDREN WITH CHRONIC PYELONEPHRITIS AT EARLY STAGES OF THE CHRONIC KIDNEY DISEASE - Vakulenko, L.I.; Abaturov, A.Ye.; Kunak, О.V. (World of Medicine and Biology, 2019)
The purpose of the study was to determine the features of the left ventricular geometry in children with chronic pyelonephritis at the initial stages of the CKD. The tendency towards a gradual increase of the left ventricular cavity with the chronic kidney disease progression has been established, so that in patients of group 3 the end-diastolic index and the end-systolic index were significantly different from the statutory indices. A statistically significant increase in the of myocardial mass index was recorded in patients of the 1 st (p = 0.02), 2nd (p = 0.016) and 3rd (p
Keywords: children; chronic pyelonephritis; chronic kidney disease; hypertrophy of the left ventricle